Reducing drug induction time in the field immobilization of elephants - Richard Hoare (Pachyderm)
Reviews field techniques, dart type, and drug dosage used over a five year research period during which 65 elephant were successfully immobilized and handled in the savanna habitat in northern Zimbabwe. 58 of the animals were immobilized by personnel supported by a fixed aircraft with observer and pilot in radio contact with the ground crew. The other seven were darted from a helicopter. The author suggests a standardized initial darting technique, a high dosage of M99 which seems to induce lateral recumbency, and quick revival of any animal seen to be in difficulty. Examples of problems encountered by others who have written in recent issues of Pachyderm are noted in the light of the authors experiences.